Prarencana Unit Alat Distilasi Minyak Sereh Kapasitas 1 Ton Daun Sereh - Saronto Saronto (Balai Besar Kimia dan Kemasan, 1976)
The object of this design is to prepare a preplan Citronella Oil Distillating Apparatus for home industry,with 1 ton fresh leaves of Androppogon nardus L batch-capacity. The apparatus resulted has a simple aperation condition,safe and able to produce Citronella Oil that meet the standard. The rendement resulted is good and it can be constructed in the machine workshops . The other important factors to be considered in constructingthis aparatus are technical factor and cost, which are describe in this paper.